Studi Sistem Informasi Manajemen: Kasus Indomaret - Nita Khairani Siregar; Rayyan Firdaus (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Indomaret, Indonesia's largest mini market, uses a management information system (SIM) for its sales. When it comes to utilizing SIM, Indomaret employs a variety of methods, including the acquisition of business and personnel in the ritel sector. The process of using the operational Indomaret SIM and implementing it for business purposes is an important aspect. Because of this, the purpose of this article is to investigate a variety of SIM Indomaret features. In order to address a variety of Indomaret functions, including inventories, logistics, SDM, keuangan, and penjualan management, the SIM was developed with the help of a large and persistent Estonian market. The SIM Indomaret system includes hardware such as a hard drive, a memory stick, a database, and software such as a computer and a telephone.